Biochemical markers and cells count in peripheral blood in patients with tuberculosis according to CYP2C9 genotype - P. B. Antonenko (Кубанский научный медицинский вестник, 2014)
The aim of present work was detection of peculiarities of pulmonary tuberculosis course depending on cytochrome-450 2C9 (CYP2C9) polymorphism according on cellular content of cells count and biochemical markers of the blood. it was done analysis of 83 medical card of primary pulmonary tuberculosis at the beginning and at the end of in-patient treatment in Odessa district dispensary in 2012 y. At the beginning and at the end of in-patient treatment the patients with genotype *2/*3, *3/*3 have had the highest level of erythrocytes and hemoglobin, and the lowest level of erythrocytes sedimentation rate that witnessed the slight intoxication. Also in this group of patients it was found the highest level of alanine aminotransferase and gamma glutathione transferase that have proved higher risk of toxicity of antituberculosis therapy in the carriers of *2/*3, *3/*3 genotype relatively to carriers of *1/*1, *1/*2, *1/*3 genotypes.